2019
DOI: 10.1111/1745-9133.12472
|View full text |Cite
|
Sign up to set email alerts
|

Why have public mass shootings become more deadly?

Abstract: Research Summary: Public mass shootings in the UnitedStates have become substantially more deadly over time.We document this increase, offer a model to explain it, review supporting evidence for the model, and present new findings on offenders from 1966 to 2019. It appears that societal changes have led to more public mass shooters who are motivated to kill large numbers of victims for fame or attention, as well as to more shooters who have been directly influenced by previous attackers. They often spend exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…In total, 1225 people were killed in a mass shooting over the past 53 years with more than half occurring in the last decade, a function of increases in mass shootings and weapon lethality [62,63,75]. Public mass shooting fatalities and injuries far outpace population growth [75].…”
Section: Principal Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 1225 people were killed in a mass shooting over the past 53 years with more than half occurring in the last decade, a function of increases in mass shootings and weapon lethality [62,63,75]. Public mass shooting fatalities and injuries far outpace population growth [75].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Because our study specifically targeted the federal legislation, we omitted state-level gun policies such as state-level prohibitions on certain types of guns, LCMs, or more lethal types of bullets. It is likely that the internet serves as a contagion and as a guide to potential mass shooters, allowing them to access weapons and multiple stories about other mass shooters [62,67,89,90].…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the prominence of social exclusion in previous shootings, it is likely shooters will reference exclusion in their manifestos. While we expect that shooters may reference explicit episodes of social rejection, bullying, and instability, we also consider the possibility that the language of exclusion may take the form of attention seeking given that research has demonstrated that fame‐seeking behavior is a common component of mass shooters’ motivations (Bushman 2018; Lankford 2016a, 2016b; Lankford and Silver 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Perpetrators who are so mentally disturbed that they have no grasp of reality would not be a good fit for Granovetter's model. However, even if they are depressed or paranoid, most public mass shooters demonstrate the ability to make rational decisions (when purchasing weapons, selecting targets, planning their attacks, creating legacy tokens, and/or seeking notoriety) that do involve assessing costs and benefits and attempting to maximize their utility (Capellan & Silva, 2021; Lankford & Silver, 2020). Furthermore, Granovetter (1978) suggests threshold-zero “radicals” care more about rioting than about their personal safety and may be labeled “demented” if they are not followed (pp.…”
mentioning
confidence: 99%